Long PCR-ribotyping of nontypeable Haemophilus influenzae. - Smith-Vaughan, H C (1995)
PCR-ribotyping, a new typing method based on long PCR, has been developed for nontypeable Haemophilus influenzae (NTHi). Ribosomal operons of NTHi were amplified by long PCR and were found to be highly polymorphic for internal HaeIII sites. The technique was applied to 49 isolates previously subjected to conventional ribotyping, and the two methods showed a high level of concordance for serial isolates from individual subjects. PCR-ribotyping provides a powerful new typing tool for strain characterization in epidemiological investigations of NTHi.